Globally Declining Population of Women Folk Causing Sex Imbalance Is a Serious Concern: An Analysis of Sex Ratio around the Globe. (12th May 2015) - Gautam, Rajesh K.; Jhariya, Jyoti; Kumar, Pardeep
Abstract : Successful existence and perpetuation of any species depend on its reproductive success. In case of humans, the theoretical proportion of males and females should be 1 : 1, but this equilibrium was disturbed in many parts of the world. What are the determinants of sex imbalance in human should be found out to combat the problem. The data were gathered for 227 countries. The sex ratio for human population of the world was found 101 males for 100 females, but it varies from 74 to 219 among the countries. The number of countries having higher number of females as compared to males is 132, as they have 99 or less males per 100 females, whereas in 71 countries the total population of males is greater than the females. And only 24 countries have balanced sex ratio. Regression analysis shows that fertility, rate of natural increase, mortality, and gender inequality index have inverse effect, and they account for 24.4%, 23.1%, 18.8%, 18.9%, 16.3%, 16.1%, and 5.1% of variability, respectively. There is great need to identify such countries and region where sex selective abortion is being practiced and to find out appropriate strategies to combat such problem.